Dynamic Coordination via Organizational Routines - Paul Heidhues; Andreas Blume; April Franco (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We investigate dynamic coordination among members of a problem-solving team who receive private signals about which of their actions are required for a (static) coordinated solution and who have repeated opportunities to explore different action combinations. In this environment ordinal equilibria, in which agents condition only on how their signals rank their actions and not on signal strength, lead to simple patterns of behavior that have a natural interpretation as routines. These routines partially solve the team's coordination problem by synchronizing the team's search efforts and prove to be resilient to changes in the environment by being ex post equilibria, to agents having only a coarse understanding of other agents' strategies by being fully cursed, and to natural forms of agents' overconfidence. The price of this resilience is that optimal routines are frequently suboptimal equilibria.
Keywords: B21; C72; L23; 330